Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.4038/jas.v12i2.8227
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Processed Aerial Yam (Dioscorea bulbifera) and Sensory Properties of Paste (Amala) Prepared with Cassava Flour

Abstract: Aerial yam is a member of the Dioscoreaceae family which consist several varieties found in South

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
(37 reference statements)
1
8
0
4
Order By: Relevance
“…However the supplementation of aerial yam flour to wheat flour was accepted upto 60%. Kayode et al (2017) also confirmed the supplementation of 60-80% of aerial yam flour for use in flour formulations for desirable sensory characteristics.…”
Section: Overall Acceptability Of Cookiessupporting
confidence: 55%
“…However the supplementation of aerial yam flour to wheat flour was accepted upto 60%. Kayode et al (2017) also confirmed the supplementation of 60-80% of aerial yam flour for use in flour formulations for desirable sensory characteristics.…”
Section: Overall Acceptability Of Cookiessupporting
confidence: 55%
“…When compared with other tuber crops, the BD of anchote flour was higher than BD of Dioscorea dumetorum and Dioscorea bulbifera (0.50-0.62 g/cm 3 ) (Abiodun, Adegbite, & Oladipo, 2010;Kayode et al, 2017). However, it is less than the BD of yam (1.14 g/cm 3 ) and cocoyam (0.94-1.01 g/cm 3 ) flours (Falade & Okafor, 2015;Nina et al, 2017).…”
Section: Bulk Density (Bd)mentioning
confidence: 80%
“…Furthermore, the variation in BD could be due to differences in particle size and moisture content of the flours (Chandra, Singh, & Kumari, 2015) which might be associated with the effect of predrying treatment and drying temperature. When compared with other tuber crops, the BD of anchote flour was higher than BD of Dioscorea dumetorum and Dioscorea bulbifera (0.50–0.62 g/cm 3 ) (Abiodun, Adegbite, & Oladipo, 2010; Kayode et al., 2017). However, it is less than the BD of yam (1.14 g/cm 3 ) and cocoyam (0.94–1.01 g/cm 3 ) flours (Falade & Okafor, 2015; Nina et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the recently reported studies on the edible D. bulbifera centred on its nutritional properties, phytochemical composition, toxicity and bitterness 12 16 , physicochemical properties of its composite with cassava flour 17 , and elemental composition of the tuber 18 . No literature yet exists on biochemical composition and a possible attempt to valorise the wild variety of D. bulbifera .…”
Section: Introductionmentioning
confidence: 99%